Atomic layer deposition of perovskites—Part 1: Fundamentals of nucleation and growth. Issue 1 (26th December 2019) - Bin Afif, Abdulla; Dadlani, Anup L.; Burgmann, Stephanie; Köllensperger, Peter; Torgersen, Jan
Abstract: A broad spectrum of accessible functionalities and material properties based on slight changes in crystal structure and composition makes perovskites a unique class of materials. Understanding and leveraging of its properties have resulted in its use in a myriad of applications. Today, performance and efficiency demands require these materials in miniaturized devices; hence, a precise control of perovskite synthesis in terms of thickness, crystallinity, and stoichiometry is indispensable. Atomic layer deposition (ALD) makes these requirements potentially conceivable due to the technology's unique self‐limiting deposition process. Yet, not all properties of perovskites have been leveraged in the thin film regime due to limited understanding of their synthesis. In part one of a two‐part review, we discuss the ALD growth of perovskite‐based thin films. After explaining the specific growth characteristics of ALD perovskites, effects of process parameters, and thin film treatments on properties, we discuss an important functional perovskite strontium titanate (STO). In part two, we discuss ALD‐deposited perovskites for next generation electronic applications.